Measuring the cellular memory B cell response after vaccination in patients after allogeneic stem cell transplantation - Winkler, Julia; Tittlbach, Hannes; Schneider, Andrea; Buchstaller, Corinna; Mayr, Andreas; Vasova, Ingrid; Rösler, Wolf; Mach, Michael; Mackensen, Andreas; Winkler, Thomas (Annals of Hematology, 2020)
After allogeneic hematopoietic stem cell transplantation (HSCT), patients are repetitively vaccinated to reduce the risk of infection caused by the immune deficiency following allogeneic HSCT. By the vaccination of transplanted patients, the humoral memory function can be restored in the majority of cases. It is unknown, however, to what extent memory B cells derived from the donor contribute to the mobilization of antibody-secreting cells and long-term humoral memory in patients after allogeneic HSCT. We therefore analyzed patients after allogeneic HSCT for memory B cell responses 7 days after single vaccination against tetanus toxoid (TT), diphtheria toxoid (DT), pertussis toxoid (PT), Haemophilus influenzae type b (Hib), and poliovirus. Patients showed an insufficient mobilization of plasmablasts (PB) after vaccination, whereas healthy subjects (HD, n = 13) exhibited a significant increase of PB in the peripheral blood. Regarding vaccine-specific antibody-secreting PB, all HD responded against all vaccine antigens, as expected. However, only 65% of the patients responded with a measurable increase in IgG-secreting PB against TT, 65% against DT, 33% against PT, and 53% against poliovirus. Correspondingly, the antibody titers on day 7 after vaccination did not increase in patients. A significant increase of serum titers for the vaccine antigens was detectable in the majority of patients only after repetitive vaccinations. In contrast to the low mobilization of vaccine-specific PB after vaccination, a high number of PB before vaccination was detectable in patients following allogeneic HSCT. High frequencies of circulating PB correlated with the incidence of moderate/severe chronic GVHD. In summary, patients showed a weak mobilization of antigen-specific PB and an inadequate increase in antibody titers 7 days after the first vaccination. Patients with moderate or severe chronic GVHD in their history had a significantly higher percentage of IgG-secreting PB prior to vaccination. The antigen specificity of these IgG-secreting PB is currently unknown.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Allogeneic stem cell transplantation; Memory B cells; Plasmablast; Vaccination after transplantation